2019
DOI: 10.1002/bit.26917
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional spherical gelatin bubble‐based scaffold improves the myotube formation of H9c2 myoblasts

Abstract: Microenvironmental factors including physical and chemical cues can regulate stem cells as well as terminally differentiated cells to modulate their biological function and differentiation. However, one of the physical cues, the substrate's dimensionality, has not been studied extensively. In this study, the flow‐focusing method with a microfluidic device was used to generate gelatin bubbles to fabricate highly ordered three‐dimensional (3D) scaffolds. Rat H9c2 myoblasts were seeded into the 3D gelatin bubble‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In addition, we found that the progression of H9C2 cardiomyoblast differentiation was also accompanied by a gradual increase in p38 activation over time, which has been shown to inhibit the activation of ERK1/2 and to induce cell cycle arrest in adult mammalian cardiomyocytes [42]. Furthermore, and in accordance with previous studies, our study documented the increased phosphorylation of Akt in the differentiating H9C2 cells, which is an important mediator of protein synthesis, a critical process for the completion of myogenic differentiation [40,41] (Figure 2C-E).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we found that the progression of H9C2 cardiomyoblast differentiation was also accompanied by a gradual increase in p38 activation over time, which has been shown to inhibit the activation of ERK1/2 and to induce cell cycle arrest in adult mammalian cardiomyocytes [42]. Furthermore, and in accordance with previous studies, our study documented the increased phosphorylation of Akt in the differentiating H9C2 cells, which is an important mediator of protein synthesis, a critical process for the completion of myogenic differentiation [40,41] (Figure 2C-E).…”
Section: Discussionsupporting
confidence: 91%
“…Myogenic differentiation is a highly orchestrated process driven by multiple signal transduction and mechanotransduction pathways, which coordinate the balance between muscle growth and atrophy [24,36,[39][40][41]. Cell cycle arrest and morphological alterations appear to accompany the differentiation process of the cardiomyocyte-like H9C2 cells [3].…”
Section: Discussionmentioning
confidence: 99%
“…Myoblasts were used to generate spheroids as such a culture provides an environment that facilitates myogenic differentiation due to a 3D structure improving physical interactions, differentiation and fusion of myoblasts Chiron et al, 2012 ; Corona et al, 2012 ; Mei et al, 2019 ; Kim et al, 2020 . One million myoblasts per genotype and per mouse were pelleted at 300 g for 5 min in 15 mL centrifuge tubes before pellets were transferred into individual wells of a six-well plate containing 50% proliferation medium (20% foetal bovine serum, Gibco 10500–064; 10% horse serum, Gibco 26050–088; 0.5% chicken embryo extract, Seralab CE-650-J; penicillin / streptomycin, Sigma P0781; in DMEM) and 50% DMEM (Gibco 31885–023) and cultured for 24 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Three-dimensional cell culture approaches can be classified as scaffold-based and scaffold-free strategies. In general, scaffold-free cell delivery can be divided into three basic methods which are single-cell delivery (Mao et al, 2017;Kamperman et al, 2017a;Lienemann et al, 2017;Qiu et al, 2018;Carvalho et al, 2015;Mei et al, 2019), cell sheet engineering, and microtissue technology (Kelm and Fussenegger, 2010). Microtissues are cell aggregates with a spheroidal shape and diameters between 100 and 500 μm.…”
Section: Introductionmentioning
confidence: 99%